Question
upstudy study bank question image url

Simplity the -lollowing \( \frac{2^{x+2}-2^{x+1}}{2^{x}+2^{x+2}} \quad \frac{b) 2 \cdot 3^{x}+3^{x-2}}{5 \cdot 3^{x+1}-7 \cdot 3^{x-1}} \)

Ask by Bowers Robbins. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) 2/5 (b) 1/6

Solution

We will simplify each expression step by step. Expression (a):   (2^(x+2) – 2^(x+1)) / (2^x + 2^(x+2)) 1. Rewrite the numerator:   2^(x+2) – 2^(x+1) = 2^x · 2^2 – 2^x · 2^1 = 2^x(4 – 2) = 2^x·2 = 2^(x+1). 2. Rewrite the denominator:   2^x + 2^(x+2) = 2^x + 2^x · 2^2 = 2^x(1 + 4) = 2^x·5. 3. Cancel the common factor 2^x:   (2^(x+1))/(2^x·5) = (2^(x)·2)/(2^x·5) = 2/5. So, the simplified form of (a) is 2/5. Expression (b):   (2·3^x + 3^(x–2)) / (5·3^(x+1) – 7·3^(x–1)) 1. Factor the numerator:   2·3^x + 3^(x–2) = 3^(x–2)(2·3^2 + 1) = 3^(x–2)(2·9 + 1) = 3^(x–2)(18 + 1) = 19·3^(x–2). 2. Factor the denominator:   First, express each term in terms of 3^(x–1):    3^(x+1) = 3^(x–1)·3^2 = 3^(x–1)·9.    3^(x–1) remains as is.   Thus, the denominator becomes:    5·(3^(x–1)·9) – 7·3^(x–1) = 3^(x–1)(45 – 7) = 38·3^(x–1). 3. Now, simplify the fraction:   (19·3^(x–2)) / (38·3^(x–1)) = (19/38) · 3^[(x–2)–(x–1)] = (19/38) · 3^(–1). 4. Since 19/38 simplifies to 1/2:   (1/2) · 3^(–1) = 1/(2·3) = 1/6. So, the simplified form of (b) is 1/6. Final Answers:  (a) 2/5  (b) 1/6

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To simplify the first expression \( \frac{2^{x+2}-2^{x+1}}{2^{x}+2^{x+2}} \), we can factor out common terms: The numerator can be simplified as: \( 2^{x+2} - 2^{x+1} = 2^{x+1}(2 - 1) = 2^{x+1} \). The denominator can be simplified as: \( 2^{x} + 2^{x+2} = 2^{x}(1 + 2^{2}) = 2^{x}(1 + 4) = 5 \cdot 2^{x} \). So the entire expression simplifies to: \[ \frac{2^{x+1}}{5 \cdot 2^{x}} = \frac{2^{x+1}}{5 \cdot 2^{x}} = \frac{2}{5} \] Now for the second expression \( \frac{2 \cdot 3^{x}+3^{x-2}}{5 \cdot 3^{x+1}-7 \cdot 3^{x-1}} \): We can start by simplifying the numerator: \( 2 \cdot 3^{x} + 3^{x-2} = 3^{x-2}(2 \cdot 3^{2} + 1) = 3^{x-2}(18 + 1) = 19 \cdot 3^{x-2} \). Then simplify the denominator: \( 5 \cdot 3^{x+1} - 7 \cdot 3^{x-1} = 5 \cdot 3^{x+1} - 7/3 \cdot 3^{x} = 5 \cdot 3^{x} \cdot 3 - 7 \cdot 3^{x} = (15 - 7) \cdot 3^{x} = 8 \cdot 3^{x} \). Putting it together, we have: \[ \frac{19 \cdot 3^{x-2}}{8 \cdot 3^{x}} = \frac{19}{8} \cdot \frac{1}{3^{2}} = \frac{19}{72} \] So, 1. The first simplified expression is \( \frac{2}{5} \). 2. The second simplified expression is \( \frac{19}{72} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy